The Emission Characteristics of a CI Engine Fueled with a Biofuel Blend - Ilkilic, C. (Taylor & Francis Inc, 2012)
In this study, an alternative diesel fuel, of which chemical modification was made by transesterification with short chain methyl alcohols, was produced from cottonseed oil. The modified products were then evaluated according to their fuel chemical properties as compared to diesel fuel. The purpose of this study is to investigate the emission characteristics of the fuel blend of 75% cottonseed oil methyl ester with 25% diesel fuel in a single cylinder unmodified diesel engine. The effects of biofuel and diesel fuel blend on a direct injected, four strokes, and single cylinder diesel engine exhaust emissions were studied. The results showed on the emissions of the engine that there was about 36% reduction in CO, about 18% reduction in CO2, and about 15% reduction in NOx. These results show that B75 fuel has better emission characteristics than diesel fuel. The reduction exhaust emissions made B75 a suitable alternative fuel for diesel engines and could help in controlling air pollution.
Keywords: alternative fuels; biofuel; cottonseed oil methyl ester; diesel fuel; emissions